2009
DOI: 10.1103/physrevb.79.125413
|View full text |Cite
|
Sign up to set email alerts
|

Continuum model for the long-range elastic interaction on stepped epitaxial surfaces in2+1dimensions

Abstract: In heteroepitaxy, the mismatch of lattice constants between the crystal film and the substrate causes misfit strain and stress in the bulk of the film, driving the surface of the film to self-organize into various nanostructures. Below the roughening transition temperature, an epitaxial surface consists of facets and steps and changes its morphology by lateral motion of steps. In this paper, we present a 2 + 1-dimensional continuum model for the long-range elastic interaction on stepped surface of a strained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…The continuum model is able to predict linear instability of a uniform step train and evolution of a stepped surface in the nonlinear regime, which are in agreement with the results of the discrete model. Zhu, Xu, and Xiang [22] performed linear instability analysis and numerical simulations using the 2+1 dimensional continuum model. Dal Maso, Fonseca, and Leoni [5] and Fonseca, Leoni, and Lu [9] proved the existence and regularity of weak solutions of Xiang and E's 1+1 dimensional continuum model [19,20].…”
Section: Monopole At Stepmentioning
confidence: 99%
“…The continuum model is able to predict linear instability of a uniform step train and evolution of a stepped surface in the nonlinear regime, which are in agreement with the results of the discrete model. Zhu, Xu, and Xiang [22] performed linear instability analysis and numerical simulations using the 2+1 dimensional continuum model. Dal Maso, Fonseca, and Leoni [5] and Fonseca, Leoni, and Lu [9] proved the existence and regularity of weak solutions of Xiang and E's 1+1 dimensional continuum model [19,20].…”
Section: Monopole At Stepmentioning
confidence: 99%
“…The first term in E m [h] is the traditional expression of the misfit elastic energy above the roughening transition temperature on surfaces [3,10,21,23]. The second term in E m [h] is the contribution to the step line energy from the force monopole interaction, and this additional term incorporates the atomic feature of the stepped surfaces [26][27][28][29].…”
Section: Preliminary and Main Resultsmentioning
confidence: 99%
“…Instability analysis and the numerical simulations based on this continuum model performed by Xiang and E [27] showed that this continuum model is able to correctly describe the step bunching instabilities compared with the results of discrete models and experimental observations. Xu and Xiang [28], Zhu, Xu and Xiang [29] further developed a 2+1 dimensional continuum model for the stepped surfaces with elastic effects, which is able to account for both the step bunching and step meandering instabilities as well as their competition. Kukta and Bhattacharya [12] proposed a three-dimensional model for step flow mediated crustal growth under stress and terrace diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…We will derive a continuum model from the discrete model given in equation (2.8). The derivation method is a generalization of those used to obtain continuum models for the Peach-Koehler force on dislocations in a single slip plane [46,53] and the elastic interaction on epitaxial surfaces [45,48,49,55].…”
Section: Outline Of the Derivationmentioning
confidence: 99%